Spontaneous hemoperitoneum due to ruptured myoma vessels in a nulliparous woman - Owusu Atta, Junior; Owusu Atta, Senior; Amponsah-Tabi, Seth; Opoku-Achampong, Emmanuel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Spontaneous hemoperitoneum due to ruptured myoma vessels is a rare but potentially life-threatening condition. A 37-year-old nulliparous black West-African woman presented in hypovolemic shock with a tender and distended abdomen. During exploratory laparotomy, a large fundal subserosal myoma with an actively bleeding vein was identified yielding 2.2 l of hemoperitoneum for which myomectomy and peritoneal lavage was done. This case underscores the importance of considering spontaneous rupture of myoma vessels as a differential diagnosis of acute abdomen in women with uterine fibroids. Rapid diagnosis and surgical management are essential to prevent morbidity and mortality.